Top 100 Most Influential Manuscripts in Congenital Abdominal Pediatric Surgery: A Bibliometric Analysis - Ka Siu Fan; Kristie Hin Chi Leung; Ka Hay Fan; Jeremy Chan (Wolters Kluwer Medknow Publications, 2021)
Bibliometric analysis identifies the most influential manuscripts that shape our understanding of various congenital gastrointestinal pathologies. This study sets out to analyse the 100 most cited manuscripts on congenital gastrointestinal surgery. The Thomson Reuters Web of Science database was searched for all manuscripts relevant to paediatric congenital gastrointestinal surgery. The number of citations, authorship, publication date, journal of publication, institution and country were recorded for each paper. Eigenfactor and impact factor rankings were obtained for each journal of publication. 971 eligible manuscripts were returned by the search. Within the top 100 manuscripts, the most cited paper (by Metkus et al.) investigated fetal diaphragmatic hernia and was cited 413 times. University of Indianapolis had the most publications (n=5) and Journal of Pediatric Surgery had the most citations (n=3231). The country with the most publications in top 100 were the USA (n=39). The most commonly published topics were diaphragmatic hernia (n=23), abdominal wall defect (n=20) and atresia (n=6). The most cited manuscripts include various topics with a primary focus on the aetiology, diagnosis, management and outcome of diaphragmatic hernia and abdominal wall defects. Additionally, by collecting the most influential works, this study serves to reference what makes a manuscript 'citable'.